A vida dos animais, de J. M. Coetzee, na Casa de Espelhos - Sobral, Pedro Aurélio Tenório (2016)
The purpose of this text is to analyze the novel The lives of animals, by South-African professor and novelist, J. M. Coetzee, having metafiction as a focus. The lives of animals is constructed upon two striking reports resulting from lectures delivered by J. M. Coetzee at Princeton University, in the United States, in 1997; eventually, Coetzee transformed that material into a novel, giving voice to the writer – his seminal character and alter ego – Elizabeth Costello. These are two lectures in which the writer defends the basic rights of non-human animals. Besides this, J. M. Coetzee’s work calls our attention to the metaficcional devices employed in the narratives. For the discussion of metafiction, we use Hutcheon (1980; 1991) and Waugh (1984). We employ metaficcional principles in the analysis of Coetzee’s text, not merely as an illustration, but to verify how important and lasting this arrangement is in contemporary literature. Since The lives of animals is a novel in which both the life and rights of non-human animals are in the foreground, we articulate metareference with theories about power relations, so as to corroborate the cruelty inflicted on non-human animals. The results presented reveal both the relevance and adequacy of metafiction in the relationship between ethics and aesthetics.